2018
DOI: 10.1128/aac.01379-18
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-Driven Evolution of Pseudomonas aeruginosa in the Presence of either Ceftazidime or Ceftazidime-Avibactam

Abstract: Ceftazidime-avibactam is a combination of β-lactam/β-lactamase inhibitor, the use of which is restricted to some clinical cases, including cystic fibrosis patients infected with multidrug-resistant , in which mutation is the main driver of resistance. This study aims to predict the mechanisms of mutation-driven resistance that are selected for when is challenged with either ceftazidime or ceftazidime-avibactam. For this purpose, PA14 was submitted to experimental evolution in the absence of antibiotics and in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 64 publications
(66 reference statements)
8
83
0
Order By: Relevance
“…BepR/NalD is a member of the TetR helix-turn-helix (HTH) family of transcription factors that contain an N-terminal DNA binding domain. The corresponding C22R amino acid substitution in the CZA-resistant isolates is located in the HTH domain, suggesting the possibility that DNA binding might be disrupted, resulting in transcriptional derepression of MexAB-OprM, as has been noted in other studies (53,54).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…BepR/NalD is a member of the TetR helix-turn-helix (HTH) family of transcription factors that contain an N-terminal DNA binding domain. The corresponding C22R amino acid substitution in the CZA-resistant isolates is located in the HTH domain, suggesting the possibility that DNA binding might be disrupted, resulting in transcriptional derepression of MexAB-OprM, as has been noted in other studies (53,54).…”
Section: Resultssupporting
confidence: 58%
“…Among the remaining 12 mutations in the CZA-resistant isolates, three other genes known to be associated with the development of antimicrobial resistance-mexB, bepR, and clpA-contained single nonsynonymous substitutions (53,54). MexB is an MDR family efflux pump that, when overexpressed, can confer resistance to multiple classes of antimicrobials in P. aeruginosa, including CZA, and numerous studies have demonstrated the evolution of resistance in association with mutations in the mexB gene (53)(54)(55)(56). A P326L substitution was present in the MexB protein in a position adjacent to the channel domain in the crystal structure (PDB accession no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While deletion of mepM1 leads to reduced MIC values of ␤-lactam antibiotics, deletion of ctpA leads to hyperresistance, probably by deregulating the levels of its substrates. The role of deleted or nonfunctional CtpA in mediating hyperresistance is further supported by the findings of a study by Sanz-García et al, who showed that upon ceftazidime-avibactam treatment, mutations in the ctpA gene emerge and that these lead to resistance (49). Additional deletion of mepM1 in the ctpA mutant reduces MIC values compared to those for the ΔctpA mutant for PIP and ATM but results in still higher MIC values compared to those for the mepM1 deletion mutant, indicating that other CtpA-dependent EPs also contribute to the upregulation of ampC expression.…”
Section: Discussionmentioning
confidence: 79%
“…In addition to genes already known to be involved in P. aeruginosa intrinsic resistance to aminoglycosides, we identified two novel loci (glnD and mucD) in the chromosome of P. aeruginosa PA14 that contribute to intrinsic resistance to at least one aminoglycoside (see Table S1 in the supplemental material), although inactivation of mucD increases susceptibility to one aminoglycoside and reduces susceptibility to another. Interestingly, both genes have been proposed to play a potential role in ␤-lactam resistance (26,36). Further, 14 novel loci could potentially be involved in the acquisition of mutational resistance to at least one aminoglycoside, since their inactivation increases the MICs of such aminoglycosides by at least 3-fold compared with the wild-type parental strain.…”
Section: Discussionmentioning
confidence: 99%